1990
DOI: 10.1111/j.1532-5415.1990.tb03505.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Impact of Urinary Incontinence in the Community‐Dwelling Population

Abstract: Ph6,f and i A n d r e w Fantl, MDSoss of urinary control can have a sigmficant impact on the psychological and social well-being of the affected individual. Research has con-L centrated on the prevalence, etiology, and management of urinary incontinence, but relatively little is known about the effects of this chronic condition on psychosocial functioning in daily life.This article reviews the literature related to psychosoaal impact of urinary incontinence in the communitydwelling adult population. The focus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
223
3
17

Year Published

1998
1998
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 295 publications
(256 citation statements)
references
References 18 publications
9
223
3
17
Order By: Relevance
“…The tolerance of UI varies significantly from individual to individual, and the impact of UI on everyday life is not directly related to any objectively measured degree of UI. 22 A woman's personal assessment of the severity of UI is modified by several factors, including age, symptom severity, type of UI, and mental state. 23 It is probable that patients with cervical carcinoma who have undergone chemotherapy and radical surgery have a diminished reaction to the severity of urinary symptoms; thus, the introduction of a specific and validated quality-of-life questionnaire regarding UI may improve the detection of urinary symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…The tolerance of UI varies significantly from individual to individual, and the impact of UI on everyday life is not directly related to any objectively measured degree of UI. 22 A woman's personal assessment of the severity of UI is modified by several factors, including age, symptom severity, type of UI, and mental state. 23 It is probable that patients with cervical carcinoma who have undergone chemotherapy and radical surgery have a diminished reaction to the severity of urinary symptoms; thus, the introduction of a specific and validated quality-of-life questionnaire regarding UI may improve the detection of urinary symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…For example, one study found that patients with detrusor instability and sensory urgency were more anxious than patients with other types of incontinence. 34 However, we suspect that considering all types of UI together makes it more difficult to find any association with distress and may have biased our results toward the null. Fourth, there is the potential for all the sources of error associated with retrospective interview data including imperfect recall and response bias (e.g., socially desirable responding).…”
mentioning
confidence: 88%
“…Symptoms of urinary frequency, urgency and urge incontinence are embarrassing for those affected and thus women with such symptoms are often reluctant to seek advice and treatment [6,7]. This is illustrated by the results of the present study, which showed low levels of baseline knowledge of urinary symptoms.…”
Section: Discussionmentioning
confidence: 58%